Static analysis 17th international symposium, SAS 2010, Perpignan, France, September 14-16, 2010 : proceedings - Cousot, Radhia; Martel, Matthieu (Lecture notes in computer science, 2010)
This book constitutes the refereed proceedings of the 16th International Symposium on Static Analysis, SAS 2010, held in Perpignan, France in September 2010. The conference was co-located with 3 affiliated workshops: NSAD 2010 (Workshop on Numerical and Symbolic Abstract Domains), SASB 2010 (Workshop on Static Analysis and Systems Biology) and TAPAS 2010 (Tools for Automatic Program Analysis). The 22 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 58 submissions. The papers address all aspects of static analysis including abstract domains, bug detection, data flow analysis, logic programming, systems analysis, type inference, cache analysis, flow analysis, verification, abstract testing, compiler optimization and program verification.